VIOLATIONS OF INTERNATIONAL LAW BY THE GOVERNMENT OF AUSTRALIA IN PRACTICE OF TURN BACK THE BOAT MANAGEMENT POLICY FOR ASYLUM SEEKERS - Jufri, Modhy Mahardika (Indonesian Journal of International Law, 2017)
Conflicts in several countries in Asia resulted in increasing number of refugees and asylum seekers. The need for protection and a decent life makes them willing to take any way to get protection in other countries, including by being illegal migrants. Australia, as a destination country for asylum seekers, imposed Operation Sovereign Borders by intercepting and returning ships carrying asylum seekers to protect the border while reducing the rate of illegal migrants coming into the country. In practice, this policy violates various provisions of international law, namely the principle of non-refoulement, human rights law, SAR obligation, the handling of migrant smuggling and violations of Indonesia sovereignty.